2019
DOI: 10.1101/gr.247353.118
|View full text |Cite
|
Sign up to set email alerts
|

One minute analysis of 200 histone posttranslational modifications by direct injection mass spectrometry

Abstract: DNA and histone proteins define the structure and composition of chromatin. Histone posttranslational modifications (PTMs) are covalent chemical groups capable of modeling chromatin accessibility, mostly due to their ability in recruiting enzymes responsible for DNA readout and remodeling. Mass spectrometry (MS)-based proteomics is the methodology of choice for large-scale identification and quantification of protein PTMs, including histones. High sensitivity proteomics requires online MS coupling with relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 39 publications
(51 reference statements)
0
41
0
Order By: Relevance
“…The AGC target for the tSIM-MSX scans was set to 10E6. The full description of the DI-MS acquisition method has been previously described (83).…”
Section: Histone Derivatization Mass Spectrometry and Ptm Quantificmentioning
confidence: 99%
“…The AGC target for the tSIM-MSX scans was set to 10E6. The full description of the DI-MS acquisition method has been previously described (83).…”
Section: Histone Derivatization Mass Spectrometry and Ptm Quantificmentioning
confidence: 99%
“…Evidence gathered from core histone PTMs have shown that patient samples and cell lines had a different PTM profile, underscoring the need to characterize PTMs from clinical samples [ 110 ]. For high-throughput studies in clinical samples including paired tissue tumor samples, approaches based on isobaric labeling, MALDI imaging, or the recently developed direct-injection mass spectrometry (DI-MS) [ 111 ] could be used. Analysis of PTMs from patient samples instead of cultured cell lines would potentially uncover new PTM marks associated with disease.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%
“…In the last decade, mass spectrometry has offered a more accurate large-scale quantitative analysis of histone modifications than the traditionally used Western blot (Völker-Albert et al, 2018). A new mass spectrometry method for histone posttranslational modification (PTM) analysis provides the possibility of high throughput screening of 200 PTMs in less than a minute (Sidoli et al, 2019a). Furthermore, methods that combine metabolomics and histone PTM analysis have already been developed for acetyl-CoA and histone acetylation (Sidoli et al, 2019b).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%